A convenient one-pot nanosynthesis of a C(sp2)–C(sp3)-linked 3D grid via an 'A2 + B3' approach. Issue 27 (25th June 2019) - Wei, Ying; Luo, Mengcheng; Zhang, Guangwei; Lei, Jiaqi; Xie, Ling-Hai; Huang, Wei
Abstract : The synthesis of fluorene-based3D-grid-FTPA, which shows excellent chemical, thermal, and photo-stabilities, has been developed using a one-pot Friedel–Crafts reaction. Abstract : Fluorene-based3D-grid-FTPA was synthesised with a total yield of 55% via the one-pot formation of six C(sp 2 )–C(sp 3 ) bonds through a BF3 ·Et2 O-mediated Friedel–Crafts reaction of A2 -type bifluorene tertiary alcohol (BIOH) and two B3 -type triphenylamines. At the same time, Un-grid-FTPA (2.7%) and2D-grid-FTPA (5.6%) were obtained as by-products from this synthesis method. In addition, the effect of stereoisomers of BIOH was evaluated to demonstrate that Rac -BIOH is a better A2 -type building block to prepare3D-grid-FTPA in a relatively high yield. Furthermore, 3D-grid-FTPA showed excellent chemical, thermal, and photo-stabilities.